2019
DOI: 10.1016/j.jsps.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of momilactones A and B to diabetes inhibitory potential of rice bran: Evidence from in vitro assays

Abstract: This study was the first to detect the presence of the two compounds momilactone A (MA) and momilactone B (MB) in rice bran using liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS). By in vitro assays, both MA and MB exhibited potent inhibitory activities on pancreatic α-amylase and α-glucosidase which were significantly higher than γ-oryzanol, a well-known diabetes inhibitor. Remarkably, MA and MB indicated an effective inhibition on trypsin with the IC 50 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 55 publications
5
48
1
Order By: Relevance
“…Isolated MA and MB were confirmed and identified by previous reports [12][13][14]. By UPLC-ESI-MS, extracted ion chromatograms showed a good separation of MA and MB, in which, MA was detected at 3.78 min with a major ion m/z 315 and MB was eluted at 2.33 min with a major ion m/z 331, see Supplementary data, Figures S1 and S2.…”
Section: Confirmation Of Ma Mb and Tricinsupporting
confidence: 81%
See 4 more Smart Citations
“…Isolated MA and MB were confirmed and identified by previous reports [12][13][14]. By UPLC-ESI-MS, extracted ion chromatograms showed a good separation of MA and MB, in which, MA was detected at 3.78 min with a major ion m/z 315 and MB was eluted at 2.33 min with a major ion m/z 331, see Supplementary data, Figures S1 and S2.…”
Section: Confirmation Of Ma Mb and Tricinsupporting
confidence: 81%
“…To date, momilactones A and B have been recognized to have valuable effects on human health comprising antidiabetic [12], anti-obesity [13], anticancer [31][32][33], and antioxidant and antiaging properties. Momilactones A and B have been quantified by various techniques but mostly by HPLC [12,13,34]. In previous studies, we found that the sensitivity of MA and MB quantifications by HPLC could be enhanced by applying the SEP-PAK C18 cartridge in preparation of the rice husk sample [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations